The plateau of trials: modern ethnicity in Angola - Martins, Vasco (2016)
This thesis is a study about the modern ethnicity of the Ovimbundu of the central highlands of Angola. It shows how Ovimbundu conceptions of ethnicity became altered and enhanced by processes of modernisation, usually introduced by foreign agents, and how this modernisation came to play a critical role after independence. Following a contrast in existing literature between either the attribution of vital importance to ethnicity in human agency or the downplay of it in favour of other elements, this work may be positioned in the middle, that is, it finds common ground with both arguments. I follow a constructivist approach, patent throughout the thesis and much used by many academic studies, which enables the analysis of Ovimbundu modern ethnicity by crossing the several influences the people of the central highlands were exposed to with their own agency and capacity to imagine and follow new ideas, mostly associated with modernisation. A paradigm begins emerging, one that recurs to the experiences apprehended during colonialism, influenced by processes of evangelisation and colonisation, which allow a clearer and more complete comprehension of aspects pertaining to the organisation of the political movements, the civil-war and issues related with post-war reconciliation, integration and state-formation. It becomes clear that the construction and imagination of political identities was much dependent upon processes of ethnic modernisation, which are still influential in people’s lives in contemporary Angola.